New Perspectives for Environmental Policies Through Behavioral Economics - Beckenbach, Frank; Kahlenborn, Walter (Springer International Publishing : Imprint: Springer, 2016)
This book presents essential insights on environmental policy derived from behavioral economics. The authors demonstrate the potential of behavioral economics to drive environmental protection and to generate concrete proposals for the efficient design of policy instruments. Moreover, detailed recommendations on how to use "nudges" and related instruments to move industry and society toward a sustainable course are presented. This book addresses the needs of environmental economists, behavioral economists and environmental policymakers, as well as all readers interested in the intersection between behavioral economics and environmental policy.